MAXIMAL COVERING METHOD IN DETERMINING DISTRIBUTION CENTERS IN DISASTER LOGISTICS - Koç, Murat; Sarıkaya, Hüseyin Ali (Journal of Industrial Engineering (Turkish Chamber of Mechanical Engineers), 2024)
Efforts to determine the location of a physical object, known as the location problem, are not new. For centuries, people have solved location problems and found various methods by formulating problems or somehow trying to optimally place objects and service centres in relation to other objects and service centres. Facility location decisions of emergency service centres such as schools, hospitals, fire brigades, disaster response points have an important place in the strategic planning of the activities of public and private organisations. In this study, it is aimed to determine the places where the necessary materials will be stored in order to meet the needs of disaster victims such as food, shelter, clothing and first aid in case of a disaster that may occur in our country. Within the framework of this purpose, the study has been carried out by taking into consideration the Turkish Red Crescent (TRC) disaster warehouses, disaster map and the disasters experienced in recent years. In Izmir Regional Disaster Management Centre (RDMC) selected as an example, first the coverage distances of each Red Crescent RDMC according to the criteria of response to the disasters, then the candidate points representing the potential warehouse locations and the demand points showing the disasters that the Red Crescent RDMC should respond to have been determined by using the Geographical Information System (GIS). While determining the most appropriate locations of the warehouses to be established, the Maximum Covering Location Problem has been selected from the facility location problem types. Six different scenarios have been created for the developed model, optimal solutions have been obtained for each scenario using ArcGIS Route Solver software and the solutions have been analyzed by changing the problem parameters.